DEVELOPMENT OF AN INTERACTIVE E-MODULE BASED ON CONSTRUCT 2 FOR EDMODO LEARNING MATERIAL IN VOCATIONAL HIGH SCHOOL: A DESIGN AND VALIDATION STUDY - Deny Ardiansah; Nurna Listya Purnamasari (JoEICT (Jurnal of Education And ICT), 2026)
The proliferation of mobile devices in educational settings has created significant opportunities for the development of interactive digital learning materials. However, the availability of engaging, context-appropriate electronic modules (e-modules) for vocational secondary school students in Indonesia remains limited, particularly for Digital Simulation and Communication subjects. This study aimed to develop and validate an interactive e-module based on Construct 2 software for Edmodo learning material targeting tenth-grade students at SMKN 2 Tulungagung, Indonesia. The Research and Development (RD) approach was adopted, guided by the ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation). The developed e-module was deployed as an Android-compatible application incorporating multimedia elements such as text, illustrations, animations, and interactive navigation. Validity was assessed through expert validation by a media specialist and a subject matter expert, followed by small-group (n = 5) and large-group (n = 20) student trials using structured questionnaires. Results demonstrated high feasibility scores: media expert validation yielded 83%, subject matter expert validation 93.8%, small-group trial 83%, and large-group trial 82.25%, producing an overall average of 85.5%, classified as "Very Eligible" according to the established feasibility rubric. These findings indicate that the Construct 2-based e-module constitutes a technically sound and pedagogically appropriate learning resource for vocational students. The study contributes a replicable development framework for creating mobile-first instructional media in resource-constrained educational contexts. Future research should examine the direct effects of the e-module on student learning outcomes, engagement, and self-regulated learning behavior through quasi-experimental designs